Cords and Chords: Exploring the Role of E-Textiles in Computational Audio - Stewart, Rebecca (Frontiers in ICT, 2019)
Electronic textiles (e-textiles) have played a significant role in computational audio ranging from wearable interfaces for creative expression to more utilitarian purposes such as acoustic monitoring for military applications. This article looks at e-textiles within computational audio from three perspectives: the historical developments of the field; the core enabling technologies; and the primary application areas. It closes with a discussion of what role e-textiles may play in future computational audio systems.